The effectiveness of forecast‐based humanitarian assistance in anticipation of extreme winters: a case study of vulnerable herders in Mongolia. Issue 1 (3rd September 2021) - Gros, Clemens; Easton‐Calabria, Evan; Bailey, Meghan; Dagys, Kadirbyek; de Perez, Erin Coughlan; Sharavnyambuu, Munguntuya; Kruczkiewicz, Andrew
Abstract : This paper presents evidence relating to a forecast‐based cash and non‐food item distribution among vulnerable herder households during the 2017–18 dzud (extreme winter) season in Mongolia, and analyses the results of a quasi‐experimental study evaluating its impacts. An innovative approach in disaster risk reduction, forecast‐based financing (FbF) can have short‐ and long‐term benefits to vulnerable households but remains understudied. The paper contributes information on a multimodal FbF programme offering one‐off cash grants and in‐kind veterinary kits. The data found significant effects of reduced mortality and increased offspring survival in some types of livestock, and that the timing of FbF assistance is crucial, as reported early assistance correlated to positive outcomes in terms of reduced animal mortality. These findings can be used to design more effective FbF interventions, to understand better the appropriateness of FbF designs, and to use early warnings and early actions to help people prepare and withstand disasters such as dzuds . الملخص: تقدم هذه المقالة أدلة على التوزيع النقدي المستند إلى التنبؤات وأدوات رعاية الحيوانات بين أسر الرعاة الضعيفة خلال فترة 2017‐2018 الشتوية (الشتاء القارس) في منغوليا، وتحلل نتائج دراسة شبه تجريبية لتقييم آثارها. يمكن أن يكون للنهج المبتكر في الحد من مخاطر الكوارث، والتمويل القائم على التنبؤ (FbF) آثار إيجابية قصيرة الأجل وطويلة الأجل للأسر المعرضة للخطر ولكن لا يزال غير مدروس. تساهم هذه المقالة بمعلومات حول برنامَج (FbF) متعدد الوسائط يقدم منحًا نقدية لمرة واحدة ومعدات بيطرية عينية. وجدت البيانات آثارًا كبيرة لتقليل معدل الوفيات وزيادة بقاء النسل في بعض أنواع الماشية، ووجدت أن توقيت مساعدة (FbF) أمر بالغ الأهمية، حيث أن طلب المساعدة مبكرا يرتبط بالنتائج الإيجابية لتقليل معدل وفيات الحيوانات. يمكن أن تساهم هذه النتائج في تصميم تدخلات FbF أكثر فاعلية، وفهم أفضل لمدى ملاءمة تصاميم FbF، واستخدام التحذيرات المبكرة والإجراءات المبكرة لمساعدة الناس على الاستعداد للكوارث ومقاومة الكوارث مثل الزود (فصول الشتاء شديدة القسوة). 摘要: 本文提供了蒙古2017‐2018年极端冬季期间，基于预测的现金和动物护理包在脆弱牧民家庭中的分发证据，并分析了一项评估其影响的准实验研究的结果。减少灾害风险和基于预测的融资(FbF)的创新方法对弱势群体的家庭能产生积极的短期和长期影响，但仍有待研究。本文提供了一次性现金赠款和兽药实物包的多模式FbF项目的信息。数据发现，在某些类型的牲畜中，降低死亡率和提高后代存活率具有显著效果，并发现FbF的帮助至关重要，因为报道的早期援助与降低动物死亡率的结果是积极相关联的。这些发现可以帮助设计更有效的防雨干预措施，更好地理解防雨设计的适宜性，并利用早期预警和早期行动帮助人们准备和抵御暴风雪等类的灾害。